Information Security Using Steganography: A Review - Monika, (International Journal of Computer Sciences and Engineering, 2025)
In modern era of communication there is lot of information exchange and every one need more and more secure communication. In order to provide secure communication stenography is widely used. The present paper provides conceptual framework on stenography that became basis for secure communication. Stenography is process of hiding secret information in any other message and provide secures communications. It consists of cover, hiding process, and un-hiding process along with channel on sender and receiver side. Stenography is implemented with the use of secret data in files. In first phase concept of stenography has been discussed & represents definition of stenography, working of stenography respectively. Existing research and benefits of stenography have been discussed in second phase respectively. Discussion has been made on designing techniques of stenography in order to enhance security. Next phase is considering challenges to existing researches have been explored in this paper. Such analysis would be beneficial to consider better enhancement in existing security mechanism. As there would be more probability of advance research if limitations of existing work is considered. At end of research in Last phase scope of research has been discussed.